A case study for developing and operating sustainable resorts : innovative sustainability practices for the next generation of green resort managers - Singh, A. J. (SAGE Business Cases., 2013)
The case study describes the development and operation of Maho Bay Camps, an eco-resort on St. John in the U.S. Virgin Islands. The story of the resort in←cludes the vision of its entrepreneurial founder, Mr. Stanley Selengut, who was originally trained as a civil engineer and used his background in engineering to develop a sustainable resort. The sustainability policies and practices pioneered at Maho Bay have been emulated in various resorts across the Caribbean and other countries and provide various learning outcomes for industry and students in hospitality management interested in developing and managing green resorts.